EXPECTATIONS REGARDING ALCOHOL CONSUMPTION IN COLOMBIAN UNIVERSITY STUDENTS - Londoño Pérez, Constanza; García Hernández, Wilson; Valencia Lara, Sandra Carolina; Vinaccia Alpi, Stefano (Anales de Psicología / Annals of Psychology, 2005)
The present study tries to describe the expectations that university students of the city of Bogotá (Colombia) have concerning alcohol consumption and evaluate its effects on the type of consumption that they present. The sample includes non-consumers, moderate consumers, dependent consumers and malignant consumers. In order to evaluate the consumption level, the questionnaire Alcohol Use Disorders Identification Test (AUDIT) is used and, to evaluate the expectations the Spanish version of the Inventory of Expectations of Alcohol Consumption (AEQ) is applied, analyzing the psychometric conditions of these tests for this population. Gender differences are evaluated in relation to the two mentioned variables. Results confirm the determining role that expectations play regarding the alcohol consumption level, and significant gender differences regarding alcohol intake and expectations relative to substance effect. In addition it is there is evidence of the predominance of expectations associated to positive effects and the facilitation of social interactions.